IMPLEMENTASI KEPROFESIONALITAS POLRI DALAM MELAKSANAKAN TUGAS BERDASARKAN PERATURAN KODE ETIK PROFESI POLRI (Faculty of Law, University of Palembang, 2022)
Violence is often carried out by the police during investigations to obtain confessions from suspects. This behavior has become a habit that can be shown from various research results, which is caused by the absence of an investigative supervisory agency, incomplete legal instruments, protection from institutions, and unprofessional attitude from the police. This situation causes the suspect to have no opportunity to fight for his rights and the perpetrators of violence are not touched. Professionalism is related to moral issues that are standardized into a code of ethics, and a violation of the code of ethics indicates that there are moral problems within the police. There needs to be a moral improvement on investigators so that the investigation can take place properly and correctly as expected. In addition, there are several regulations that regulate the police professional code of ethics, Peraturan Kapolri Nomor 14 Tahun 2011 Tentang Kode Etik Profesi Kepolisian Negara Republik Indonesia so that it cannot be applied arbitrarily and can carry out its duties properly in accordance with the police code of ethics.